Aplikasi Guided Imagery Terhadap Nyeri Pada Pasien Gastritis Di Wilayah Kerja Puskesmas Cijedil Kabupaten Cianjur - Novi Noerasyah Jamil; Sri Kurnia Dewi (Lentera : Jurnal Ilmiah Kesehatan dan Keperawatan, 2021)
Gastritis is an inflammation of the gastric mucosa that causes acute pain so that it can interfere with the daily activities of people who experience it. Acute pain is an unpleasant sensory and emotional experience resulting from actual and potential tissue damage. The purpose of this study is to reduce pain guided imagery therapy. This research uses case study method. Participants were taken as many as one respondent, namely clients who experienced gastritis with acute pain nursing problems. The results showed that the client experienced a decrease in the pain scale which initially received a scale of 5 to 3. Based on these results, it can be concluded that guided imagery therapy has an influence on reducing the pain scale.